Application of capillary electrophoresis for the assay of erythromycin and its related substance - Lalloo, Anita Kantilal (Rhodes University, Faculty of Pharmacy, Pharmacy, 1997)
Capillary Electrophoresis (CE) is a high resolution analytical technique that may be employed in the separation and quantification of a wide range of analytes. The enormous efficiency obtained in CE are well suited for complex mixtures in which resolution of a large number of peaks in a short time is desirable. Therefore, CE has a promising future in pharmaC-eutical analysis. The separation mechanism of CE is based on the differential electrophoretic mobility of the solutes inside a buffer filled capillary upon the application of a voltage. Capillary electrophoresis is especially suitable for ionic species. The full potential of this technique can only be realised through the manipulation of numerous experimental parameters. In the present study, a CE method has been developed for the analysis of the macrolide antibiotics: erythromycin, oleandomycin, troleandomycin and josamycin. The selection of initial analysis conditions and optimisation of selectivity are reviewed. A systematic approach to method development was used to maximise analyte differential electrophoretic mobilities, by adjusting the pH. Thereafter, the influences of electrolyte molarity and electrolyte additives were investigated. In addition, some instrumental parameters, such as capillary length emf diameter, applied voltage and injection conditions were varied. The effect of the sample solvent and oncapillary concentration techniques such as FASI, were investigated. Also, the influence of injecting a water plug on the quantity of sample injected was demonstrated. Full resolution was achieved with the addition of methanol to the electrolyte. The applicability of CE for the assay of erythromycin and its related substances was investigated. Two methods were developed and successfully validated using CE: one for the quantitative determination of erythromycin alone and another for erythromycin related substances in the presence of large quantities of erythromycin A. Several related substances and impurities that result from the fermentation process used to produce erythromycin as well as degradation products are known to be present in commercial sa~ples. These impurities include erythromycin B, C, D, E, F, erythromycin enol ether, anhydroerythromycin and N-demethylerythromycin. Currently both the USP and BP official assays for the analysis of erythromycin involve the use of microbiological assays. These methods are limited as they are unable to differentiate between erythromycin and its related substances and degradation products. Furthermore, the microbiological assays are time-consuming and tedious to perform. 11 The CE methods developed for the analysis of erythromycin and for its related substances were fully validated in terms of precision, linearity, accuracy, sensitivity and stability. In addition, erythromycin was subjected to six stress modes and the stressed samples were analysed. An intemal standard was employed to provide acceptable precision for the migration time Â« 1.80 % RSD) and peak area Â« 4.44 % RSD). Optimum sensitivity was obtained using low UV wavelengths, with LOO values of less than 10 % for the related substances. The developed method was accurate for erythromycin C, anhydroerythromycin and N-demethylerythromycin, even in the presence of large concentrations of the parent. The method for~ erythromycin related substances was applied to the determination of impurities in three commercial erythromycin bases. The CE methods developed were rapid, precise, specific and stability-indicating and may be used to provide additional information to augment that attained by HPLC for purity assessment and in stability studies of erythromycin. Capillary electrophoresis is a simple, cost-effective technique that is capable of generating high quality data. This technique will become firmly established within pharmaceutical analysis for main peak and related impurity determination assays as familiarity becomes more widespread across the pharmaceutical industry and improvements in instrumentation are performed.
Keywords: Antibiotics -- Analysis; Capillary electrophoresis; Erythromycin -- Analysis